Development and evaluation of an MRE-based absorber with two individually controllable natural frequencies. (31st July 2018) - Yang, J; Sun, S S; Chi, J Y; Ning, D H; Du, H; Zhang, S W; Li, W H; Mao, S X
Abstract: Adaptive tuned mass absorbers, which are based on magnetorheological elastomer (MRE) have been widely accepted for vibration absorption due to their frequency shift capability. Wider frequency bandwidth indicates more effectiveness in reducing vibrations. In order to broaden the effective bandwidth of the MRE-based absorber, this study proposes a new design consisting of an eccentric mass. This design enables the absorber to have two natural frequencies: the rotational natural frequency and the translational one. These two natural frequencies can be controlled separately by adjusting the MRE stiffness and the eccentric length. This design not only broadens the effective bandwidth of the absorber, but enables the absorber to suppress vibrations with multiple dominant frequencies. The characterization experiment verifies the existence of the two natural frequencies and draws the conclusion that the translational natural frequency is under the influence of the applied current, while the rotational natural frequency is controlled by both the applied current and the eccentric length. The vibration reduction effectiveness is then evaluated experimentally by mounting the MRE-based absorber on a primary system.